To evaluate this expression:
-21 ÷ (1/3) ÷ (-7) × 5 ÷( -2/3) × 2 [1]
We need to remember the PEMDAS procedure:
First, solve parentheses, then exponents; then, multiplications, divisions, and finally additions and subtractions.
However, in this case, we will start to solve this expression from the left to the right (in the order the operations started, that is, from left to right):
-21 ÷ (1/3) ÷ (-7) × 5 ÷( -2/3) × 2
First step:
-21 / 1/3 = -21 * 3 = -63
-63 ÷ -7 = 9
We multiply this result by 5:
9 x 5 = 45
45 ÷ (-2/3) = 45 x -(3/2) = -135/2
(-135/2) * 2 = -135
We chose to evaluate this way because it was the order in which appeared each operation, that is, from left to right.
This is a way of evaluating this expression.